IBM SISTEM INFORMASI ZAKAT, INFAQ DAN SODAQOH (SIMZIS) ONLINE BAGI PANTI ASUHAN - Februariyanti, Herny; Sasongko Wibowo, Jati; Wibisono, Setyawan (Proceeding Fakultas Ekonomi, 2014)
The main problems of the data management faced by orphanages is the conventional system management services to charity, donation, alms conventional system. Conventional service management issues that donor data collection, data collection and administrative transactions carried occupants with manual records. Search data and history of the old inhabitants who had left the orphanage, donated the use of data archiving is a common problem. The solution offered is to build Zakat Management Information Systems, Infak and sodaqoh (SIMZIS) with stages: (1) Method of building and implementing IBM Information Management System Zakat Infak and sodaqoh (SIMZIS), using the method of participatory action research on community service partners, activities and involvement of partners, partner participation; (2) The implementation of the activities and involvement of partners with stage situation analysis and identification, prototype development of management information systems, training, pilot implementation, guidance, mentoring and consultation, monitoring and evaluation, implementation SIMZIS; (3) Participation partner with IBM team well as policy makers and as participants.